(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2023)
A study of the clinical and epidemiological features of tuberculosis of extrapulmonary localizations in Uzbekistan for the period from 2020 to 2023 was conducted .A steady growth trend of the bone subgroup has been revealed. - articular tuberculosis with a dominant lesion of the spine has been proven to be a prognostic disease.